THE EFFECT OF GIVING MORINGA LEAF CONSUMPTION ON PREGNANT WOMEN WITH ANEMIA - Muliani, Rima (Journal of Midwifery Tiara Bunda, 2025)
Background: Anemia in pregnancy is a condition in which the mother has a hemoglobin level below 11 g% in the first and third trimesters or a level <10.5 g% in the second trimester. Globally, the prevalence of anemia in pregnant women is 41.8%. The prevalence of anemia in pregnant women is estimated at 48.2% in Asia, 57.1% in Africa, 24.1% in America, and 25.1% in Europe. According to data from the 2018 Basic Health Research (Riskesdas), there are 48.9%. Anemia is influenced by several factors, one of which is poor diet. A balanced diet consists of various foods in appropriate amounts and proportions to meet a person's nutritional needs. Moringa is a plant that is very easy to find in Indonesia and usually grows as a supporting plant in yards. Moringa is rich in nutrients because all parts of the Moringa plant are very beneficial for people's lives.It is used as a food and medicine. One of the most prominent contents of the Moringa plant is the antioxidants in its leaves. Another benefit is increasing hemoglobin levels in the blood. Objective: This study aims to determine the effect of oxytocin massage on increasing breast milk production in breastfeeding mothers. Methods: This study employed a quantitative design. The design used was a pre-experimental design using aone-group pretest-posttest approach with 30 respondents using a purposive sampling technique. Results: The Wilcoxon test showed that hemoglobin levels in pregnant women before and after being given Moringa leaves were p-value 0.001 (p-value <0.05). Conclusion: Therefore, it can be concluded that there was an increase in hemoglobin levels after administering tomato juice to pregnant women in the independent midwife practice of LH Tangerang Regency in 2025.